DETERMINING THE OPTIMAL ROUTE OF BULOG RICE DISTRIBUTION USING SEQUENTIAL INSERTION AND NEAREST NEIGHBOUR METHOD - Yayang Safitri; Fibri Rakhmawati; Rima Aprillia (Program Studi Teknik Informatika Universitas Khairun, 2024)
Rice consumption in Indonesia is the 4th highest in the world, with an annual average of 35.3 million tonnes. Apart from that, domestic rice production is relatively low, so finding an optimal distribution pattern to meet Indonesia's food consumption needs is necessary. This research aims to find the best route for rice distribution using sequential insertion and nearest-neighbor methods. The aim is to compare the two methods to determine which is suitable for distributing rice. Apart from that, comparisons are made to find the distribution route with the shortest distance and fastest time. The research results show that the optimal travel distance using the sequential insertion method is t = 1, namely 519 Km with a travel time of 779 minutes. Meanwhile, the optimal travel distance using the nearest neighbor method at r = 1 is 506 km with a travel time of 535 minutes. Thus, this problem's nearest neighbor method performs better than sequential insertion.